Evolution of arterial hypertension in patients with hepatitis C virus cirrhosis after antiviral treatment - Toma, Letitia; Mercan-Stanciu, Adriana; Zgura, Anca; Bacalbasa, Nicolae; Diaconu, Camelia; Iliescu, Laura (International Journal of Advances in Medicine, 2020)
Background: Chronic hepatitis C (HCV) infection has direct and indirect manifestations that promote vascular resistance. On the other hand, HCV infection leads to liver cirrhosis and complications such as cardiomyopathy, characterized by a hyperdynamic state with low peripheral vascular resistance. The aim of this paper is to study the evolution of arterial hypertension in patients with liver cirrhosis, after the cure of HCV infection. Methods: This is a prospective observational cohort study including 261 hypertensive patients with compensated HCV cirrhosis who underwent direct-acting antiviral treatment. Blood pressure was monitored at the initiation of antiviral therapy and at 3, 6 and 12 months follow-up. Screening for cirrhosis complications was performed and patients were also monitored by electrocardiography, liver and kidney function tests, serum lipids and N-terminal pro-B-type natriuretic peptide. Results: Virologic response after antiviral treatment led to a better control of arterial hypertension with a decrease of 24 hours mean blood pressure by 15% (p=0.04, CI 95%). In patients with stable liver disease serum levels of N-terminal pro-B-type natriuretic peptide slowly decreased at 6 and 12 months (p=0.02, p=0.03), while in patients with cirrhosis decompensation the levels increased. Also, patients with decompensated cirrhosis presented lower blood pressure values and required discontinuation of antihypertensive drugs. Conclusions: Curing HCV infection may lead to a better control of blood pressure in patients with compensated liver disease. However, an abrupt decrease in blood pressure may be a clinical sign of progressive liver disease and cirrhotic cardiomyopathy.